Arsenic Speciation in Algae: Case Studies in American Continent - Pastene-Olivares, R; Pastene-Olivares, R (Elsevier B.V., 2019)
The objective of this chapter was to obtain information about arsenic speciation in algae studied in American Continent and Antarctic. This matter supposes deliver information with respect to accumulation, biotransformation and toxic effect on human health. Arsenic speciation in algae has become one of the most important issues to assess the risk to human health associated with algae consumption. This chapter also include the main analytical methods for the determination of different chemical arsenic-species used commonly in American Continent and Antarctic. Finally, some countries of America Continent such as Argentina, Chile, Brazil among others, have carried out important studies on arsenic content in algae, mainly brown macroalgae. It is concluded, that is necessary to increase and pursue more researches about arsenic speciation in algae in American Continent and its effects on human health attributed to it consumption. © 2019 Elsevier B.V.